Stress tunable spin dynamics of a magnetic vortex under resonant magnetic fields - Xun Rao; Lele Peng; Weichao Yan; Yun Shen; Xiaohua Deng; Guohong Dai (AIP Advances)
In this study, we investigated the stress-controlled magnetization processes and dynamic susceptibility of a magnetic vortex in FeGa disk under an external magnetic field. Our primary objectives were to elucidate the nucleation process of a magnetic vortex and explore the modulatory effects of mechanical stress on its behavior. Our findings reveal that the applied stress can regulate the spin arrangement, leading to different hysteresis loops with kinks of different switching processes in the magnetization. Specifically, tensile stress induces a buckling state, facilitating the transition from the parallel spin to the vortex state in smaller disks and introducing a distinct kink in the hysteresis loop. Conversely, compressive stress causes the disappearance of the original intermediate state in larger disks, leading to a smoother hysteresis loop. Notably, the stress-introduced magnetic anisotropy altered the resonance region of the system. These findings offer valuable insights into the design and optimization of magnetic storage devices and magnetic field sensors, highlighting the potential of harnessing mechanical stress as a tuning parameter for enhancing their performance.